Cyanobacterial aldehyde deformylase oxygenation of aldehydes yields n-1 aldehydes and alcohols in addition to alkanes - Aukema, Kelly G. (2013)
Aldehyde-deformylating oxygenase (ADO) catalyzes O(2)-dependent release of the terminal carbon of a biological substrate, octadecanal, to yield formate and heptadecane in a reaction that requires external reducing equivalents. We show here that ADO also catalyzes incorporation of an oxygen atom from O(2) into the alkane product to yield alcohol and aldehyde products. Oxygenation of the alkane product is much more pronounced with C(9-10) aldehyde substrates, so that use of nonanal as the substrate yields similar amounts of octane, octanal, and octanol products. When using doubly-labeled [1,2-(13)C]-octanal as the substrate, the heptane, heptanal and heptanol products each contained a single (13)C-label in the C-1 carbons atoms. The only one-carbon product identified was formate. [(18)O]-O(2) incorporation studies demonstrated formation of [(18)O]-alcohol product, but rapid solvent exchange prevented similar determination for the aldehyde product. Addition of [1-(13)C]-nonanol with decanal as the substrate at the outset of the reaction resulted in formation of [1-(13)C]-nonanal. No (13)C-product was formed in the absence of decanal. ADO contains an oxygen-bridged dinuclear iron cluster. The observation of alcohol and aldehyde products derived from the initially formed alkane product suggests a reactive species similar to that formed by methane monooxygenase (MMO) and other members of the bacterial multicomponent monooxygenase family. Accordingly, characterization by EPR and Mössbauer spectroscopies shows that the electronic structure of the ADO cluster is similar, but not identical, to that of MMO hydroxylase component. In particular, the two irons of ADO reside in nearly identical environments in both the oxidized and fully reduced states, whereas those of MMOH show distinct differences. These favorable characteristics of the iron sites allow a comprehensive determination of the spin Hamiltonian parameters describing the electronic state of the diferrous cluster for the first time for any biological system. The nature of the diiron cluster and the newly recognized products from ADO catalysis hold implications for the mechanism of C-C bond cleavage.